ANALISIS KOMPOSISI TRUK PADA JARINGAN JALAN PERKOTAAN DI KOTA MAKASSAR - Lutfie, Mukhtar; Samang, Lawalenna; Sakti, Adi; Ramli, Isran (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Trucks have a significant role in transporting build materials to the infrastructure development needs in the region South of Sulawesi. Thus, the operation of the truck on the urban road network for these activities, has brought the issue concerns the environmental impact of increased traffic accidents, improvement of urban transport congestion, increased emissions and vehicle noise. In the context of understanding the extent of the contribution of trucks to the issue of the problem, it needs to be done in depth study of phenomena related to the composition of the truck traffic on the existing road network, the contribution of emissions and noise caused, contributed to the decline in road traffic performance, and significant role in infrastructure development, and will eventually be able to do an assessment of the risk level operator of the truck on the urban road network. As a preliminary study on this issue, this paper focuses on analyzing the composition of the truck traffic on urban road network with a case study in the city of Makassar. This study has conducted a survey enumeration traffic volume for 13 hours from 07:00 to 22:00 on 36 major roads in the city of Makassar. The survey results were extracted to obtain the composition of truck to volume of traffic. Furthermore analysis totruckcomposition all day performed using statistical analysis approach to look at the composition of the phenomenon is different trucks all day interurban road sections surveyed. The results show that the composition of the truck to the existing traffic volume is small enough:0,38% s/d 8,67%, where the frequency distribution level throughout the day is not the same for all arterial roads in the city of Makassar. The results in this study has provided a preliminary description of the composition of the trucks on the road network in the city of Makassar, and further studies can be used in the risk assessment operation of trucks on city streets will be done in further studies in the future.